«En busca de un submarino». Crónica a bordo del buque insignia del exilio republicano en Argentina: el Massilia - Bárbara Ortuño Martínez (Cahiers de Civilisation Espagnole Contemporaine)
This article analyses the travel chronicle on board the Massilia of Constantino del Esla, journalist and correspondent in the Spanish Civil War, that was published as chapters in November 1939 by the Argentinian journal La Nación. We will describe the concrete details of the complicated trip on board the flagship of the republican exile in Argentina, which transported the biggest group of intellectuals who entered the country without landing permit before 1940. This example will be our starting point to show the main characteristics of the attitude of Argentinian authorities towards the arrival of Spanish refugees, as well as the strategies these refugees developed in order to cross the borders.